2012
DOI: 10.1007/s00359-012-0720-7
|View full text |Cite
|
Sign up to set email alerts
|

Nematocytes’ activation in Pelagia noctiluca (Cnidaria, Scyphozoa) oral arms

Abstract: Nematocytes' discharge is triggered to perform both defense and predation strategies in cnidarians and occurs under chemico-physical stimulation. In this study, different compounds such as amino acids and proteins (mucin, albumin, poly-L: -lysine, trypsin), sugars and N-acetylate sugars (N-acetyl neuraminic acid, N-acetyl galactosamine, sucrose, glucose, agarose and trehalose), nucleotides (ATP and cAMP), were tested as chemosensitizers of nematocyte discharge in the oral arms of the scyphozoan Pelagia noctilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Notably, the chemosensitizing effect of sugars, glutathione, nucleotides and mucin was dosedependent effect. 22 More recent research 23 reported the evaluation of the activity of local anesthetic lidocaine, alcohols, acetic acid and ammonia in preventing discharge of Pelagia noctiluca nematocysts when induced by chemosensitizers (N-acetyl neuraminic acid, N-acetyl galactosamine, glutamate, artherenol, carbachol, arginine, glycine, cysteine, mucin, albumin). Excluding lidocaine which induced a slight, non significant, increase of discharge in comparison to the control, all evaluated compounds failed to induce discharge per se and, furthermore, they were able to impair the discharge induced by chemosensitizers.…”
Section: Nematocyst Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the chemosensitizing effect of sugars, glutathione, nucleotides and mucin was dosedependent effect. 22 More recent research 23 reported the evaluation of the activity of local anesthetic lidocaine, alcohols, acetic acid and ammonia in preventing discharge of Pelagia noctiluca nematocysts when induced by chemosensitizers (N-acetyl neuraminic acid, N-acetyl galactosamine, glutamate, artherenol, carbachol, arginine, glycine, cysteine, mucin, albumin). Excluding lidocaine which induced a slight, non significant, increase of discharge in comparison to the control, all evaluated compounds failed to induce discharge per se and, furthermore, they were able to impair the discharge induced by chemosensitizers.…”
Section: Nematocyst Dischargementioning
confidence: 99%
“…The discharging resulted more efficient with the combined activity of both mechanical and chemical stimuli and a dose-dependent chemosensitizing mechanism was observed after treatment with nucleotides, mucin, sugars, and glutathione. 22 Finally, in studies on the effect of pH changes on the osmotic phase (OP), regulatory volume decrease (RVD) and nematocyte discharge, Pelagia noctiluca nematocysts subjected to hyposmotic shock were seen to expand osmotically and then to regulate the volume within 15 min at pH 7.65. On the contrary, acidic values compromised the OP (pH=6.5), reduced or abrogated RVD (pH=4.5), and reduced discharge.…”
Section: Reviewmentioning
confidence: 99%
“…When an appropriate chemico-physical stimulus is applied, both tubule and toxins are promptly delivered via an exocytotic process termed discharge. Discharge is one of the most rapid biological responses known so far, whose activation mechanism has been focused on by many authors [2,3,4,5]. The first stage for discharge activation is chemosensitization, occurring via binding of exogenous compounds to chemoreceptors located on cells, other than nematocytes, modulating in turn the mechanosensitive apparatus (cilia).…”
Section: Introductionmentioning
confidence: 99%
“…The current knowledge of Pelagia noctiluca biology [17,28] and physiology [5,29,30] may allow to propose this specimen and its homeostatic features as new models to monitor the possible presence and ecological impact of marine pollutants, such as hydrocharbons and heavy metals, and ocean acidification. Concerning this latter phenomenon, it has been recently proven that acidification of the external medium significantly impairs discharge response and cell volume regulation capability following hypotonic shock (regulatory volume decrease, RVD) [20] of Pelagia noctiluca nematocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation